PERBANDINGAN TITER ANTIBODI VIRUS NEWCASTLE DISEASE YANG DIUJI MENGGUNAKAN ANTIGEN HOMOLOG DAN HETEROLOG - , RADEN LAURENTIUS GUSTAF P.D., Dr. drh. Michael Haryadi Wibowo, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Newcastle Disease(ND) is an acute respiratory disease which could infect chicken in all ages. In general, hemaglutination inhibition (HI) test in laboratories still used La Sota antigent the most. Recently the vaccine wich be used in the farm could be different to the antigen for HI test in the laboratory. To understand that different, the research was diterminated to examine of the homolog antigen compare to the heterolog one for HI test in the laboratory. This reseach used 40 broilers which were vaccinated with VG/GA live at 1 day age, and boosted using VG/GA live at 18 day age. Blood sampling were collect from brachialis vein. Serum samples which obtained titrated by hemaglutination inhibition test using VG/GA (homolog) antigen and La Sota (heterolog) antigen. Positive HI test was indicated by the capability of serum to inhibit red blood cell's hemaglutination by H protein of ND virus so there is no agregation occurs. Antibody's titer result then calculated using Geometric Mean titer (GMT) and analized using T-test to acquired its significancy. The GMT analysis shows that antibody titer which tested by VG/GA antigent is 8,1, in other hands antibody titer which tested by La Sota antigent is 1,7. T-test analysis indicated a significant result (p<0,05). From the results, can be concluded that homolog antigen produce a higher antobody titter compare the heterolog one. Hemaglutination inhibition test better done by using an antigen which similar to the vaccine, because a homolog antigen will give a higher antibody's titer than the heterolog.